The cost of uncertain life span - Edwards, Ryan D. (Working paper series / National Bureau of Economic Research, 2008)
"A considerable amount of uncertainty surrounds life expectancy at birth, the average length of life. The standard deviation in adult life spans is about 15 years in the U.S., and theory and evidence suggest it is costly. In this paper, I calibrate a standard intertemporal model to show that one less year in standard deviation is worth about half a mean life year. Differences in the standard deviation amplify measured differences in life expectancy between the U.S. and other industrialized countries, and accounting for historical gains against the standard deviation raises the total value of mortality declines during the last century by about 25 percent"--National Bureau of Economic Research web site